Bone marrow tryptase as a possible diagnostic criterion for adult systemic mastocytosis. Issue 1 (January 2016) - Bulai Livideanu, C.; Apoil, P. A.; Lepage, B.; Eischen, M.; Laurent, C.; Laharrague, P.; Lamant, L.; Tournier, E.; Tavitian, S.; Pouplard, C.; Recher, C.; Laroche, M.; et al.
Summary: Background: Mastocytosis is difficult to diagnose, especially when systemic mast cell activation symptoms are not present or involve only one extracutaneous organ. Objective: The main objective was to evaluate the accuracy of the bone marrow tryptase level in the diagnosis of systemic mastocytosis in patients with a clinical suspicion of mastocytosis. Methods: We included all adult patients evaluated in our centre between December 2009 and 2013 for suspected mastocytosis as part of a standardized procedure and who had a bone marrow and serum tryptase assay on the same day. The diagnosis of systemic mastocytosis was established on the basis of the World Health Organization criteria as the gold standard. The accuracy of the bone marrow tryptase level in the diagnosis of systemic mastocytosis was assessed by a receiver operating characteristics curve analysis. The different sensitivity and specificity values, corresponding to the set of possible bone marrow tryptase level cut‐off values, were estimated with 95% confidence intervals. Results: Seventy‐three patients were included. The diagnosis of systemic mastocytosis was established in 43 patients (58.9%). The median bone marrow tryptase level was 423 μg/L [95% CI: 217–868] in the systemic mastocytosis group and 7.5 μg/L [95% CI: 4.6–17.1] in the non‐systemic mastocytosis group ( P < 0.001). A cut‐off value of 50 μg/L for bone marrow tryptase identified systemic mastocytosis with a sensitivity of 93.0% [95% CI: 80.9–98.5%] and a specificity of 90.0% [95% CI: 73.5–97.9%]. Conclusion and Clinical Relevance: The bone marrow tryptase level appears to be a valuable diagnostic criterion for confirming systemic mastocytosis. If this diagnosis can reliably be excluded by evaluation of the bone marrow tryptase level, there would be no need to perform a bone marrow biopsy.